Development of a closed-loop recycling process for discontinuous carbon fibre polypropylene composites. (1st August 2018) - Tapper, Rhys J.; Longana, Marco L.; Yu, Hana; Hamerton, Ian; Potter, Kevin D.
Abstract: In this study the effects of a closed-loop recycling methodology are evaluated for degradation using a discontinuous carbon fibre polypropylene (CFPP) composite material. The process comprises two fundamental steps, reclamation and remanufacture. The material properties are analysed over two recycling loops. For neat polypropylene, the molecular weight analysis indicates evidence of minimal matrix degradation that does not affect the material behaviour, as demonstrated by the shear tests. CFPP specimens show no decrease in mechanical properties over repeated loops, the final specimens show an increase of 26% and 43% in ultimate tensile strength and ultimate strain, respectively. These are attributed to cumulative matrix residue on the fibre surface after reclamation and subsequently increased fibre-matrix adhesion. The improvement of CFPP properties and insignificant variability in the tensile properties and molecular weight distribution of neat polypropylene validate the potential of this proof-of-concept, closed-loop recyclable material. Future studies will investigate alternative, higher performance matrices.